Studi Literatur : Diet Kalori Surplus untuk Remaja Underweight - Kris Yusuf Kun Utomo; Brigitte Sarah Renyoet (JURNAL GIZI DAN KESEHATAN, 2022)
Behavioral changes in adolescents can result in dietary changes. Inappropriate diets such as diets that consume energy (calories) in small amounts compared to the daily nutritional needs of adolescents can cause a calorie deficit. A calorie deficit over a long period of time can lead to nutritional status problems, namely being underweight. The purpose of this study was to create a calorie surplus diet and appropriate efforts for adolescents with underweight nutritional problems in Indonesia. This research method uses literature study, collecting data from various online references. From the analysis of the results and discussion it was found that the surplus calorie diet can be provided by consuming food according to individual needs and adding calories between 200-300 kcal / day. Weight gain can occur from muscle mass growth and fat mass gain from a calorie surplus diet. For muscle mass growth, the surplus calorie diet must be balanced with resistance training and protein intake of 2 grams of protein / kg body weight / day. Estimated muscle mass growth of 1 kg in 8 weeks. The conclusion of this study is that a calorie surplus diet is given with the provision of nutritional intake according to needs that are given the right addition of calories for weight gain from muscle mass growth balanced with resistance training to overcome the problem of underweight in adolescents. ABSTRAKPerubahan perilaku pada remaja dapat mengakibatkan perubahan diet. Diet yang tidak tepat seperti diet yang mengkonsumsi energi (kalori) dalam jumlah sedikit dibandingkan dengan angka kebutuhan gizi sehari – hari remaja yang dapat menyebabkan terjadinya defisit kalori. Defisit kalori dalam periode waktu yang lama dapat mengakibatkan masalah status gizi, yaitu berat badan kurang (Underweight). Penelitian ini bertujuan untuk menjelaskan diet kalori surplus serta upaya yang tepat ditujukan kepada remaja dengan masalah gizi underweight di Indonesia. Metode penelitian ini menggunakan studi literatur, pengambilan data dari berbagai referensi secara daring. Dari analisis hasil dan pembahasan didapati bahwa diet kalori surplus dapat diberikan dengan konsumsi makanan sesuai kebutuhan individu serta penambahan kalori antara 200 – 300 kkal / hari. Pertambahan berat badan dapat terjadi dari pertumbuhan massa otot dan pertambahan massa lemak dari diet kalori surplus. Untuk pertumbuhan massa otot maka diet kalori surplus harus diimbangi dengan olahraga resistance training serta asupan protein sebesar 2 gram protein / kg berat badan / hari. Estimasi pertumbuhan massa otot sebesar 1 kg dalam 8 minggu. Kesimpulan dari penelitian ini yaitu diet kalori surplus diberikan dengan ketentuan asupan gizi sesuai kebutuhan yang diberi penambahan kalori yang tepat untuk pertambahan berat badan dari pertumbuhan massa otot dengan diimbangi dengan resistance training untuk mengatasi masalah underweight pada remaja.